The Development of a Digital Smart Book Using the Realistic Mathematics Education Approach for Statistics Material in Eighth Grade - Rinangkit, Ina; Susila, Heni Rita; Pebriantika, Leni (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
The integration of technology and pedagogy in mathematics learning remains a significant challenge, particularly in supporting students’ understanding of abstract concepts such as statistics. This study aims to develop and evaluate the validity and practicality of a Digital Smart Book based on the Realistic Mathematics Education (RME) approach for eighth-grade students. The research employed a Research and Development (R&D) design using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The study involved expert validators in content, media, and instructional design, as well as students participating in one-to-one evaluation (3 students), small group evaluation (8 students), and field testing (33 students). Data were collected through observations, interviews, and Likert-scale questionnaires, and analyzed using descriptive statistics and percentage-based feasibility criteria. The results indicate that the developed Digital Smart Book achieved a high level of validity, with an average score of 90%, categorized as very good. Specifically, content validity reached 94.5%, instructional design 89%, and media validity 87%. In terms of practicality, the product consistently showed very good results across all testing stages, with scores of 90% in one-to-one and small group evaluations, and 91% in field testing. These findings demonstrate that the Digital Smart Book is both valid and practical for use in mathematics learning. The integration of RME principles within a digital interactive medium supports meaningful and contextual learning experiences. This study contributes to the development of innovative digital learning media that align with student-centered learning and the demands of 21st-century education.